Immersion in Water During Active Labor Decreases Postpartum Hematocrit Fall Following Vaginal Delivery - Buyuk, Gul Nihal; Kahyaoglu, Serkan; Turgut, Ezgi; Yumuşak, Omer Hamid; Kose, Caner; Ustun, Yaprak (Gynecology Obstetrics & Reproductive Medicine, 2019)
OBJECTIVE: The objective of the study was to investigate the effect of immersion in water strategy during labor on postpartum bleeding by calculating the postpartum reduction rates of the hematocrit values of the patients. STUDY DESIGN: The study groups consisted of 84 women undergoing vaginal delivery with immersion in water during labor (group 1) and the control group (group 2) of 84 women undergoing normal vaginal delivery. Patients who have received additional medical and surgical interventions for alleviation of postpartum hemorrhage, patients who have undergone an episiotomy and/or perineal trauma were not included in the study. All data were taken from patients who have delivered with spontaneous vaginal delivery. Postpartum hematocrit fall rates of the groups have been compared and the effect of immersion in water on postpartum hemorrhage has been evaluated. RESULTS: The study groups consisted of 84 women undergoing vaginal delivery with immersion in water during labor (Group 1) and the control group (Group 2) of 84 women undergoing vaginal delivery at the hospital. The women in the two groups were matched with respect to age, parity, birth weight and gestational age. The mean age of the women was 29.8±4.8 and 30.5±4.9 respectively. The mean hematocrit difference in the first group was 2.08 ± 1.88 and in the second group was 3.81 ± 1.55. The mean percentage of hematocrit reduction in the first group was 5.71% and in the second group 10.23%. CONCLUSION: Our data showed that mean hematocrit level decreases among women following vaginal delivery more than women who give birth vaginally within immersion in water during labor. The percentage of hematocrit reduction in the water birth group was lower than in the control group. Water birth seems to facilitate uterine contractions more efficiently following vaginal delivery.